عالمگیریت کا تصور: عہد قدیم سے عہد حاضر تک (Al-Qamar, 2023)
ʻĀlamgīriyat Is the Urdu translation of the English term Globalization. It is the process by which a business or other organization becomes international. The concept of Globalization is ancient. The wars fought on religion and nationality were, the result of Globalization that has existed since ancient times. While in this Era media has made it so easy for man that the change in one corner of the world can be easily felt in another part. Thomas L Friedman has described three periods of Globalization; the first period is called ‘COUNTRIES AND MUSCLES’ which is limited to around 1800. The subsequent period from 1800 to 2000 is called Globalization II. The Era of Globalization 3 begins after 2000.
Keywords: Globalization; Internationalism; Ancient; Subsequent; Era; Interrupted; Dynamism; Integration; Collaborate; Period